(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
Land use studying is considered as an important part of complete planning operation, which puts an obvious viewing for future development, The importance of using Geographic Information System in land use studying, came from that it is a new and efficient method in dealing with huge part of data. It’s had high capability for analyzing data, which benefit users in reaching to right decisions, which are difficult to make with traditional methods, And that refers to what it have of integration between information, By connecting or collecting data in layers which can be dealing with automatically. The research aimed to use Geographic Information System techniques in studying land use in Kensabba province according to three levels. Produced land use maps with scales (1/100000- 1/50000- 1/30000), And put database for each level. The research put pattern of land use, and it’s various functions, And it had been cleared the influence of forest and agricultural uses on the studied area, Besides there was decrease in urban uses.